The Law of Assembly in the People's Republic of China: Implications of the Retreat to Formal Legalism for the Legislative Process in China - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 1991)
Under the most current constitution, written in 1982, the citizens of the PRC are guaranteed freedom of the press, speech, assembly, association, procession, and demonstration; furthermore, all citizens enjoy the rights and assume the responsibilities prescribed by the constitution and the law. In 1989, following the student democracy demonstrations in the PRC, the government circulated a draft of the law concerning assemblies, processions, and demonstrations for public comment. While the 24 articles of the draft legislation effectively removed the right to free public protest by interposing a variety of administrative procedures governing proscription of venue, application, approval, and review, the eventual law did make some attempt to "democratize" the process. Even so, the public security organs now have absolute power to cancel protest activities and arrest any participants or organizers and the category of areas designated as "off limits" to public assemblies has been expanded. The way in which the legislation was passed, its constitutional language, and the ascription to regulation for the protection of citizens' rights reveal the utility of legality in ensuring political legitimacy and highlight the manipulation of the legislative process in the PRC by the government as motivated by foreign policy concerns.